The Betterment of Group Dynamics in Theory of Translation Class through Lesson Study - Magfirah Thayyib (Universitas Cokroaminoto Palopo, 2019)
The understanding of group dynamics is a challenging field. It is quite often that the interaction and energy between students in the group present in negative pattern or less healthy. Lesson study is considered to be a suitable way to cope with that group dynamics problem. The objectives of this research are to describe the pattern of group dynamics in Theory of Translation class and outline the efforts done for the betterment of group dynamics through Lesson Study. The research was conducted in class 3A of third semester of English Language Education Study Program. The data of group dynamics were obtained from the observers’ sheets. While the data of the efforts done for the betterment of group dynamics were obtained from plan and reflection discussion notes, and a checklist of application. In analyzing the data, the first data were presented descriptively and made into inferences. The second data were grouped and described; then their effectiveness was analyzed qualitatively. Based on the result of the research, it is found that the group dynamics in Theory of Translation class from open class 1 – 4 went through a betterment. The efforts done for the betterment of group dynamics were distributing job and responsibility within group, delivering the whole instruction of group activities in the beginning and checking for students understanding, and providing worksheet for group work and learning media for each group.